Measurement of the charm-mixing parameter γCP - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review letters, 2019)
A measurement of the charm-mixing parameter yCP using D0→K+K−, D0→π+π−, and D0→K−π+ decays is reported. The D0 mesons are required to originate from semimuonic decays of B− and ¯¯¯B0 mesons. These decays are partially reconstructed in a data set of proton-proton collisions at center-of-mass energies of 7 and 8 TeV collected with the LHCb experiment and corresponding to an integrated luminosity of 3 fb−1. The yCP parameter is measured to be (0.57±0.13(stat)±0.09(syst))%, in agreement with, and as precise as, the current world-average value.
Im Titel ist CP tiefgestellt
Im Titel wird gamma als griechischer Buchstabe dargestellt
R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, A. Piucci, N. Skidmore, M. Stahl, S. Stemmle, U. Uwer, A. Zhelezov [und weitere] (LHCb collaboration)
Gesehen am 22.05.2019